2002
DOI: 10.1002/aqc.551
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of serpulid biogenic reef coverage of the sea bed (Polychaeta: Serpulidae) using a video transect technique

Abstract: ABSTRACT1. The large size, patchiness and fragility of serpulid reefs present difficulties for the measurement of reef coverage for mapping and monitoring studies. Video transect measures of cover are assessed in terms of accuracy and sensitivity of the method for the identification of spatial or temporal changes.2. By comparison with direct in situ measurement of reef cover, it was found that still photography was capable of providing an accurate means for the measurement of the seabed coverage by individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Similar reasons were cited for the designation of Loch Creran as a Special Area of Conservation under the EC Habitats Directive (Moore et al 2003). …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar reasons were cited for the designation of Loch Creran as a Special Area of Conservation under the EC Habitats Directive (Moore et al 2003). …”
Section: Discussionmentioning
confidence: 69%
“…The primary recommendation of this survey must be that further study of these unusual reefs is necessary. There are five areas to which research should be targeted: distribution and abundance of reefs (following the method of Moore et al 2003); ecology and life history of G. hystrix (see Kupriyanova et al 2001); reef development and history; ecology and associated fauna (especially the concept of reefs as "nurseries"); and monitoring for human impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work (Moore et al, 1998) indicated that serpulid reefs fringe the periphery of the loch in depths of 1-13 m. Preliminary trials with sidescan sonar revealed difficulty in discrimination of reef material in certain parts of the loch, especially on steeply sloping seabeds, where the serpulid band is narrow and is accompanied by other hard substrates (Moore et al, 2003). It was therefore decided to employ two approaches to reef mapping.…”
Section: Methodsmentioning
confidence: 98%
“…The intertwining tubes grow up from a substrate of rock or bivalve mollusc shell to produce roughly ovoid-shaped patch reefs (Figure 1(A), (B)) with a maximum height often exceeding 50 cm and width of 60 cm (Moore et al, 2003). However, there is great variability in reef shape.…”
Section: Introductionmentioning
confidence: 98%
“…Sonar has been used to detect small tubeworm formations in Delaware Bay [3] and for the detection and mapping of polycheate tubeworm reefs in the UK [4], [5]. Video transects have also been used for mapping serpulid reef coverage [6]. In the Coorong, Ficopomatus reefs occur at shallow depths, and in Mundoo channel these depths are generally up to 0.7 m below mean sea level, meaning that techniques such as sonar would not be suitable.…”
Section: B Remote Sensing Of Ficopomatus Reefsmentioning
confidence: 99%